Hysteroscopic Outcomes in Our Clinic: 5 Years Experience - Balcı, Osman; Karataylı, Rengin; Acar, Ali; Çapar, Metin (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: The documentation of outcomes of hysteroscopic procedures carried out at Selcuk University, Meram Medicine Faculty, Obstetrics and Gynecology Department in 2002–2006 years. STUDY DESIGN: 248 patients that have undergone hysteroscopy were included into the study. Operative indications and results were detected retrospectively. RESULTS: There were 94 primary infertile patients, in 17 of these polypectomy, in 8 patients diagnostic hysteroscopy together with laparoscopy, in 47 patients uterine septum resection and in 22 patients hysteroscopic synechiolysis for Asherman’s syndrome were carried out. There were 118 secondary infertile patients who had hysteroscopy for diagnostic purposes together with laparoscopy in 15 patients, for septum resection in 40 patients who had uterine anomaly, for habitual miscarriages in 25 patients, for polypectomy in 18 patients, for synechiolysis in 20 Asherman’s syndrome patients. There were 7 patients with dysfunctional uterine bleeding and hysteroscopic endometrial ablation was performed for these patients. In 9 patients hysteroscopy was done to take out ectopic intrauterine device. In 8 patients hysteroscopic polyp extirpation and in 12 patients hysteroscopic sub-mucosal myomectomy was performed. Among 248 hysteroscopic procedure, 8 cases were complicated with uterine rupture, there were no other major complications related to procedure, so our complication rate was 3.2%. CONCLUSION: Hysteroscopic procedures can be carried out for several indications and do not have frequent severe complication risks. The mostly seen complication is uterine rupture. In our series we have detected only 8 uterine rupture (3.2%).